2012
DOI: 10.25011/cim.v35i1.16105
|View full text |Cite
|
Sign up to set email alerts
|

Comparing health behaviours of internal medicine residents and medical students: An observational study

Abstract: Purpose: During residency, many physicians find it difficult to maintain a healthy lifestyle; however, there is little objective data available. In this study, residents’ health behaviours and cardiovascular risk status were compared with those of medical students. Methods: Medical residents (n=55, postgraduate years 1 to 4) were compared with medical students (n=62, years 1-4). The main dependent variable was the average number of steps per day (assessed using a pedometer) at work and leisure over three day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
1
12
0
2
Order By: Relevance
“…Por último, la dependencia a la nicotina parece ser baja, con una alta motivación para el cambio, por lo que este período de la vida constituye una excelente oportunidad para el cese del tabaquismo 3,7 . El consumo de tabaco en los residentes estudiados presenta una prevalencia inferior a la población general de referencia, que se aproxima al 30% de consumo diario 4,5 , y a la encontrada en otros estudios realizados sobre personal sanitario en formación, cuyo consumo oscila desde la quinta parte hasta la mitad de la población de los encuestados 10,11,15,16 , aunque similar a estudios más recientes 12,17 . Se encuentran características similares a otras poblaciones como enfermeros o estudiantes de medicina 8,9,18,19 , aunque el tabaquismo en los estudiantes de medicina en Cataluña parece ser ligeramente superior 20 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Por último, la dependencia a la nicotina parece ser baja, con una alta motivación para el cambio, por lo que este período de la vida constituye una excelente oportunidad para el cese del tabaquismo 3,7 . El consumo de tabaco en los residentes estudiados presenta una prevalencia inferior a la población general de referencia, que se aproxima al 30% de consumo diario 4,5 , y a la encontrada en otros estudios realizados sobre personal sanitario en formación, cuyo consumo oscila desde la quinta parte hasta la mitad de la población de los encuestados 10,11,15,16 , aunque similar a estudios más recientes 12,17 . Se encuentran características similares a otras poblaciones como enfermeros o estudiantes de medicina 8,9,18,19 , aunque el tabaquismo en los estudiantes de medicina en Cataluña parece ser ligeramente superior 20 .…”
Section: Discussionunclassified
“…Parece ser, pues, que los residentes adoptan con los hábitos propios de la etapa adolescente 3 y universitaria un consumo concentrado en los momentos de ocio y asociado al policonsumo 10,13 . Este consumo de tabaco se ha asociado, en algunos estudios, a unos peores hábitos de vida entre los residentes, asociados a mayor riesgo cardiovascular frente a los estudiantes de pregrado 17 .…”
Section: Discussionunclassified
“…Other studies specific to college students have found that physical activity and dietary habits are related to motivation and perceived barriers (Downes, ). In general, college and graduate students have been found not to engage in the levels of physical activity and nutritious diets recommended by the U.S. Department of Health and Human Services and the U.S. Department of Agriculture (; Downes, ; Garcia‐Williams, Moffitt, & Kaslow, ; Office of Disease Prevention and Health Promotion, U.S. Department of Health and Human Services, n.d.; Rye et al, ). However, it is not currently known how healthy lifestyle behaviors and beliefs correlate with depression and anxiety in graduate health sciences students.…”
Section: Introductionmentioning
confidence: 99%
“…[2], [28], [29] One survey of residents found that self-care activities, including exercise, were associated with the absence of burnout. [30] However, residents are less likely to exercise regularly than medical students or attendings, [21], [31] and a survey of radiology residents found that only 37% engaged in recommended guidelines for physical activity. [20] A study of military physicians found that physical fitness declined and weight increased during residency training, [32] and a study of 375 residents from two academic medical centers found that third year medical residents were more likely to be overweight than first year residents [33].…”
Section: Introductionmentioning
confidence: 99%